2021
DOI: 10.3390/polym13162607
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hydrophobic Blocks of PEO-Containing Copolymers on Glyceryl Monooleate Lyotropic Liquid Crystalline Nanoparticles for Drug Delivery

Abstract: The investigation of properties of amphiphilic block copolymers as stabilizers for non-lamellar lyotropic liquid crystalline nanoparticles represents a fundamental issue for the formation, stability and upgraded functionality of these nanosystems. The aim of this work is to use amphiphilic block copolymers, not studied before, as stabilizers of glyceryl monooleate 1-(cis-9-octadecenoyl)-rac-glycerol (GMO) colloidal dispersions. Nanosystems were prepared with the use of poly(ethylene oxide)-b-poly(lactic acid) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The release of the drug from these carriers was pH dependent and varied from 30% to 96%. Vukovic et al 7 reported a quick release of resveratrol from HEMA/alginate and HEMA/gelatin hydrogels within the first 2 h. Chaudhary et al 79 have managed to incorporate resveratrol into mesoporous silica nanoparticles achieving an encapsulation efficiency of nearly 100% and reporting a drug release of 30%–40% within 8 h. Forys et al 80 reported release of 20%–40% of resveratrol from lyotropic liquid crystalline nanoparticles prepared from glycerine monooleate (GMO) stabilized by poly(ethylene oxide)‐ b ‐poly(lactic acid) or poly(ethylene oxide)‐ b ‐poly(5‐methyl‐5‐ethyloxycarbonyl‐1,3‐dioxan‐2‐one) copolymers during first 6 h, while rest of the drug remains encapsulated inside the nanocarriers. Ionita et al 81 have reported also rather quick release of 60% of resveratrol from mesoporous silica nanoparticles in a 10‐h period, with no further release observed.…”
Section: Resultsmentioning
confidence: 99%
“…The release of the drug from these carriers was pH dependent and varied from 30% to 96%. Vukovic et al 7 reported a quick release of resveratrol from HEMA/alginate and HEMA/gelatin hydrogels within the first 2 h. Chaudhary et al 79 have managed to incorporate resveratrol into mesoporous silica nanoparticles achieving an encapsulation efficiency of nearly 100% and reporting a drug release of 30%–40% within 8 h. Forys et al 80 reported release of 20%–40% of resveratrol from lyotropic liquid crystalline nanoparticles prepared from glycerine monooleate (GMO) stabilized by poly(ethylene oxide)‐ b ‐poly(lactic acid) or poly(ethylene oxide)‐ b ‐poly(5‐methyl‐5‐ethyloxycarbonyl‐1,3‐dioxan‐2‐one) copolymers during first 6 h, while rest of the drug remains encapsulated inside the nanocarriers. Ionita et al 81 have reported also rather quick release of 60% of resveratrol from mesoporous silica nanoparticles in a 10‐h period, with no further release observed.…”
Section: Resultsmentioning
confidence: 99%
“…Fonseca-Santos B et al, have resolved the solubility issue of resveratrol to increase its therapeutic acceptability by engineering transresveratrol-loaded nonionic LLCs [89]. Similarly, Forys A and colleagues have proved that certain amphiphilic block copolymers [poly (ethylene oxide)-b-poly(lactic acid) (PEO-b-PLA) and poly (ethyleneoxide)-b-poly(5-methyl-5-ethyloxycarbonyl-1,3-dioxan-2one) (PEO-b-PMEC)] stabilizes the non-lamellar LLC nanoparticles made up of GMO colloidal dispersions loaded with resveratrol as model drug [168]. As noticed by authors, the intersection of nanotechnology and LLC has created LC nanoparticles and its unique advantages can be exploited by the application of QbD that will save time and costs, and aid in scalability [169].…”
Section: Applications Of Lyotropic Liquid Crystals In the Parenteral ...mentioning
confidence: 97%
“…The vials containing the release medium were maintained in a reciprocal shaking bath through the test (37 ± 0.5 • C, 100 rpm). At specified time intervals (2,4,6,8,10,12,18,20,22, and 24 h; 2, 3, 4, 5, 7, 10, 14, 18, 21, 28, 32 and 35 days), 2 mL of release medium was pulled out and replaced by pure PBS to maintain sink condition.…”
Section: In Vitro Release Assessmentmentioning
confidence: 99%
“…Lately, to overcome the initial burst release, lipid liquid crystals based amphiphilic materials, such as sorbitan monooleate (SMO) [9], glycerol monooleate (GMO) [10], glycerol dioleate (GDO) [11] and glycerol trioleate (GTO) [12] were used as a potential bioactive carrier for depot delivery of several active pharmaceutical ingredients (API). Various studies assessed model hydrophilic and hydrophobic drugs, such as risperidone [11], clonazepam [13], glucose [14] and paclitaxel [15], to be delivered via this depot approach.…”
Section: Introductionmentioning
confidence: 99%